Decoupling Chemical Composition from Viscoelastic Recovery in Rejuvenated Asphalt Binders - Multazam Hutabarat; Suwaphit Chamwon; Preeda Chaturabong (Civil Engineering Journal, 2026)
This study investigates the decoupling between bulk chemical composition and high-temperature viscoelastic recovery in rejuvenated asphalt binders. A pressurized aging vessel (PAV)-aged binder (AC60/70) was rejuvenated using pyrolytic bio-oils from sugarcane bagasse (SBO) and rice straw (RSO) at 5–20 wt% dosages. SARA fractionation, colloidal instability index (Ic), penetration, and multiple stress creep recovery (MSCR) testing at 0.1 and 3.2 kPa were conducted before and after a rolling thin film oven (RTFO) aging. Both bio-oils restored SARA fractions to nearly identical levels (Ic = 0.541–0.572), yet penetration diverged substantially (79 vs. 36 dmm at 20% for SBO and RSO, respectively). After RTFO aging, MSCR responses converged across all formulations regardless of pre-aging differences, yielding identical an Equivalent Single Axle Load (ESAL) classification. This convergence is attributed to selective volatilization of low-molecular-weight bio-oil components during thermal conditioning, consistent with findings from a companion rheological–fatigue study. The results reveal a fundamental decoupling: bulk chemical indices, while useful for compositional assessment, do not correspond to stress-dependent viscoelastic recovery mechanisms governing rutting resistance. Performance-based rheological testing is therefore essential for reliable evaluation of rejuvenated binders under field-relevant conditions.